2020
DOI: 10.1038/s41416-020-0886-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactate concentration in breast cancer using advanced magnetic resonance spectroscopy

Abstract: Background Precision medicine in breast cancer demands markers sensitive to early treatment response. Aerobic glycolysis (AG) upregulates lactate dehydrogenase A (LDH-A) with elevated lactate production; however, existing approaches for lactate quantification are either invasive or impractical clinically. Methods Thirty female patients (age 39–78 years, 15 grade II and 15 grade III) with invasive ductal carcinoma were enrolled. Lactate concentration was quantified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Obesity was associated with elevated serum lactate levels and enhanced the lactate production from gonadal, but not from mammary, adipocytes (Figure 5C,D). Thus, malignant breast cancers (including E0771) both produce large amounts of lactate [38][39][40] and become exposed to exogenous lactate from the adipocyte-rich microenvironment. We hypothesize that elevated lactate levels in the orthotopic tumor microenvironment (compared to the ectopic microenvironment) lead to decreased intracellular conversion of pyruvate to lactate in E0771 cells, which in turn can increase their de novo lipogenesis from glucose through an increased oxidation of pyruvate into Acetyl-CoA, which feeds into the TCA cycle.…”
Section: Adipose Tissue Co-culture or Lactate Pretreatment Led To Increased De Novo Lipogenesis From Glucose In E0771 Cellsmentioning
confidence: 99%
“…Obesity was associated with elevated serum lactate levels and enhanced the lactate production from gonadal, but not from mammary, adipocytes (Figure 5C,D). Thus, malignant breast cancers (including E0771) both produce large amounts of lactate [38][39][40] and become exposed to exogenous lactate from the adipocyte-rich microenvironment. We hypothesize that elevated lactate levels in the orthotopic tumor microenvironment (compared to the ectopic microenvironment) lead to decreased intracellular conversion of pyruvate to lactate in E0771 cells, which in turn can increase their de novo lipogenesis from glucose through an increased oxidation of pyruvate into Acetyl-CoA, which feeds into the TCA cycle.…”
Section: Adipose Tissue Co-culture or Lactate Pretreatment Led To Increased De Novo Lipogenesis From Glucose In E0771 Cellsmentioning
confidence: 99%
“…As considerable studies reveal that lactate has a vital role in tumorigenesis and progression, lactate metabolism has drawn increasing attention in recent years ( 3 ). For breast cancer, tumor lactate has been indicated as an unfavorable biomarker and was related to HER2 status and trastuzumab susceptibility ( 7 , 8 ). However, additional data and more studies were required to support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck squamous cell carcinoma, lactate was found to be inversely correlated with overall and disease-free patient survival and positively correlated with radioresistance ( 5 , 6 ). For breast cancer, it has been reported that elevated intratumoral lactate levels were an adverse prognostic factor in breast cancer ( 7 ). Furthermore, raised intratumoural lactate levels were related to HER2 addiction status and trastuzumab susceptibility in HER2-positive breast cancer ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In normal serum, lactate concentrations range from 1.5 to 3 mM ( 8 ), while tumor concentrations can range from 10 to 30 mM, reaching extremely high levels (50 mM) within necrotic tumor cores ( 9 ). Indeed, elevated levels of lactic acid indicate poor prognosis in several cancer types, including cervical ( 8 ), breast ( 10 ), head and neck ( 9 , 11 ), high-grade gliomas ( 12 ), and non–small cell lung cancer ( 13 ). Therefore, it comes as no surprise that lactic acid, especially at tumor-equivalent concentrations, has profound effects on infiltrating immune cells ( Figure 1 ).…”
Section: Lactic Acidmentioning
confidence: 99%